Measurements of Air and Snow Photochemical Species at WAIS Divide, Antarctica - Bales, Roger (IEDA: US Antarctic Program Data Center, 2014)
Abstract: This data set contains atmospheric mixing ratios of nitric oxide, ozone, hydrogen peroxide, methylhydroperoxide, and concentrations in surface snow and in snow pits of nitrate, nitrite, and hydrogen peroxide at the WAIS Divide deep ice-coring site.